Artemisia vestita: A Folk Medicine with Hidden Herbal Fortune - Shivani Dogra; Joginder Singh; Bhupendra Koul; Dhananjay Yadav (Molecules, 2023)
Traditional medicines are nature’s gift and our native heritage, which play a vital role in maintaining a disease-free life. Artemisia vestita Wall. ex Besser (family: Asteraceae), popularly known as “Kubsha” or “Russian wormwood”, is a highly enriched folklore medicine with wound- healing, antiphlogistic, antifebrile, antifeedant, anti-helminthic, antimicrobial, antiviral, antitumor, and antiproliferative potential attributed to the presence of various volatile and non-volatile secondary metabolites. A systematic and extensive review of the literature on A. vestita was carried out via the Web of Science, PubMed, INMEDPLAN, EMBASE, Google Scholar, and NCBI, as well as from several websites. The highly relevant literature contained in 109 references was selected for further inclusion in this review. A total of 202 bioactive compounds belonging to different chemical classes such as terpenoids, coumarins, flavonoids, alkaloids, acetylenes, tannins, carotenoids, and sterols have been reported in A. vestita, which are responsible for different pharmacological activities. The chemical structures obtained from the PubChem and Chem Spider databases were redrawn using the software Chem Draw® version 8.0. This review paper summarizes the distribution, botanical description, phytochemistry, pharmacological activities, and conservation of A. vestita, which will assist scientists for further investigation. Extensive studies on the active constituents, pharmaceutical standardization, mode of action, and sustainable conservation of A. vestita are needed to further explore its wound-healing and allied medicinal properties.